The field of fight: how to win the global war against radical Islam and its allies - Flynn, Michael T. (St. Martin's Press)
Al-Qaeda has morphed into a much more dangerous, menacing threat: ISIS. America is in grave danger until our government takes decisive action against the terrorists that want nothing more than to destroy us and our way of life. Flynn spent more than 33 years in Army intelligence, and has been a firsthand witness to government screw-ups, smokescreens, and censored information that our leaders don't want us to know. Here he succinctly lays out why we have failed to stop terrorist groups from growing, and what we must do to stop them